1997
DOI: 10.1021/jo962397o
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Photodimerization of Acenaphthylene

Abstract: The mechanism of photodimerization of acenaphthylene (ACN) has been investigated in order to elucidate the roles of the singlet and the triplet excited states of ACN in the formation of the Zand E-dimers in several solvents. The quantum yields and the ratio of the produced Z-to E-dimer were determined under irradiation of ACN at 435.8 nm in several solvents (1,2-dichloroethane, acetonitrile, cyclohexane, benzene, methanol, and DMF) over a wide concentration range (2.0 × 10 -4 -2.0 M) in the absence of additive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 32 publications
(61 reference statements)
6
55
0
Order By: Relevance
“…The exclusive formation of the cis dimers in aerated solvents suggests that an excimer state may intervene, similar to the behavior found for the dimerization of 4. 27 In degassed solutions, both cis and trans dimers are formed readily, which suggests that intersystem crossing (step 3) occurs with some efficiency and that the triplet state dimerizes to form both cis and trans dimers. It is notable that the cis/trans ratio in degassed cyclohexane varies only slightly from that obtained in HAS.…”
Section: Methodsmentioning
confidence: 99%
“…The exclusive formation of the cis dimers in aerated solvents suggests that an excimer state may intervene, similar to the behavior found for the dimerization of 4. 27 In degassed solutions, both cis and trans dimers are formed readily, which suggests that intersystem crossing (step 3) occurs with some efficiency and that the triplet state dimerizes to form both cis and trans dimers. It is notable that the cis/trans ratio in degassed cyclohexane varies only slightly from that obtained in HAS.…”
Section: Methodsmentioning
confidence: 99%
“…Acenaphthylene (ACN) yields two dimers upon irradiation that are stereo isomers (Scheme 1) -the syn and the anti. 26,27 The proportion of syn and the anti dimers in the product mixture is dependent on three main factors, viz. multiplicity of excited state, concentration, and polarity of medium.…”
Section: Photochemistry Of Acenaphthylene Scheme 1 Photochemistry Ofmentioning
confidence: 99%
“…A recent theoretical study concluded that the delocalization within the five‐membered ring is weak, which explains why the reactivity of the corresponding C=C double bond remains relatively high. Among the recent reactivity studies, we note an extensive investigation of its photochemical dimerization . The 1‐aza analogues are also known and have some interesting biological properties .…”
Section: Introductionmentioning
confidence: 99%
“…Among the recent reactivity studies, we note an extensive investigation of its photochemical dimerization. [3] The 1-aza analogues are also known and have some interesting biological properties. [4] To the best of our knowledge, no phosphorus analogue has ever been described, but some saturated acenaphthene analogues have been synthesized and used in asymmetric catalysis.…”
Section: Introductionmentioning
confidence: 99%